Determinants of mother to child transmission of HIV in Addis Ababa, Ethiopia - Girum Sebsibie Teshome; Lebitsi Maud Modiba (Elsevier, 2021)
Background: According to the 2019 UNAIDS reports, globally 38 million people were living with HIV (36.2 million adult and 1.8 million Children). About 25.4 million were accessing antiretroviral therapy. Only 81% knew their HIV status. About 85% pregnant women living with HIV had access to antiretroviral medicines. Objective: The purpose of this study was to assess the determinants of mother to child transmission of HIV in Addis Ababa, Ethiopia. Method: The study was conducted in three hospitals of Addis Ababa, Ethiopia. Mothers and HIV exposed infants were taken as study population. A total of 216 HIV exposed infants and mothers were selected by systematic random sampling method. Data was collected from February 2018 to April 2018. A hospital based cross-sectional study design was used for this study. Multivariate analysis was used to determine the association between dependant and independent variables. Results: According to multivariate analysis, mothers who did not disclose their HIV status for their sexual partner (AOR: 1.4, CI: 1.33-3.865, p: 0.000), HIV discordant couple (AOR: 4.021, CI: 2.380, 55.622, p: 000), maternal CD4 count/mm3 less than 350 (AOR: 8.435, CI: 2.130, 48.299, p: 000) and unknown HIV status before pregnancy (AOR = 4.562, CI: 3.168, 42.303, p = 0.000) were significantly associated with increased risk of mother to child HIV transmission. Conclusion: This study shows that mothers who didn't disclose their HIV status, HIV discordant couple, Maternal CD4 count less than 350/mm3 and unknown HIV status before pregnancy were associated with increased risk of mother to child HIV transmission.